THE IMPORTANCE OF LEARNING INDONESIAN LANGUAGE IN PRIMARY SCHOOL - Erni Eriani Panjaitan; Nurannuri Siregar (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
This article was written with the aim of providing information about the importance of learning Indonesian in higher education. Language is a means of human communication with each other. Indonesian is a national language that must be preserved and its rules must be observed. The method used in this article is the literature study method. The data obtained in this article comes from books, journals, scientific articles, and literature reviews which contain concepts appropriate to the topic raised. The result of this article is that learning Indonesian is very important for both students and universities. Because studying Indonesian at university will create a positive attitude towards Indonesian, uniting various regional languages ​​into one, Indonesian, adding a sense of pride, loyalty and nationalism towards the Indonesian state. And Indonesian is important to support each university which has a different regional language.